The development of creativity-based learning activities to enhance theatrical production skills of Thai 7th graders - Anucha Maneethip; Titiworada Polyiem (Journal of Green Learning, 2025)
This study aimed to (1) develop creativity-based learning (CBL) activities to enhance grade 7 students’ skills in theatrical production design and management based on the 70/70 efficiency criterion; (2) compare the students’ performance in theatrical production design with the 70 percent proficiency benchmark after participating in the CBL activities; and (3) investigate the students’ satisfaction with the implemented CBL activities. The research employed a quasi-experimental design using a one-group posttest-only format. The sample consisted of 34 students from grade 7/3 at Thakhonyang Pittayakhom School, Maha Sarakham province, Thailand, during the second semester of the 2024 academic year. The sample was selected using cluster random sampling with the classroom as the sampling unit. The research instruments included: (1) creativity-based learning activity plans, (2) an evaluation form for theatrical production design and management, and (3) a student satisfaction questionnaire. Data were analyzed using percentage, mean, standard deviation, and hypothesis testing through a one-sample t-test. The findings revealed that the learning plans achieved an efficiency, students’ theatrical production scores were significantly higher than the benchmark, and overall satisfaction was rated at a high level. The study contributes to the growing body of research supporting the integration of creative pedagogies in subject areas where performance and design are central.